PERANCANGAN VISUAL BRANDING “RUMAH POHON LAING PARK” - SITI FADHILAH GOBAH, Riri Trinanda, S.Pd. M.Sn., Elia Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Laing Park tree house is the first tourism destination in Solok Town using tree house theme. Laing Park tree house has many potentials, started from the pleasantness, naturalness, peacefulness and creativity. Up until now, the potentials of Laing Park tree house have not been known and realized by the majority people caused by the lack of promotion by the owner. Thus, it is needed to design the visual branding to give certain identity so that the target audience or the visitor can see and feel what image that the Laing Park tree house presents. Designing the visual branding of Laing Park tree house started with establishing the visual identity of that tourism destination such as logo, promotion media that has not been used before, and resetting the layout and the typography that will be used in the visual communication media. Those are the backgrounds that based this visual branding design.The analysis methods that is chosen in designing the visual branding od Laing Park tree house is Swot (strengths, weakness, opportunities, and threat). This method is used to find the strengths, weakness, potentials, and the danger that Laing Park tree house has also to find the distinguishing factors it has with other tourism destination.The result of designing the visual branding of Laing Park tree house is a logo that is applied in the prime media, which is a manual book of Laing Park tree house, also with the supporting media such as stationary set namely name card, envelope, letter sheet, file folder, and other supporting media such as sign syatem, infographic, safety sign, sticker, ticket, dlyer, scarf, and pin.Key search: Visual Branding, Laing Park Tree House, Logo, Sign System